2021
DOI: 10.4314/ajcem.v22i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and characterization of bacteria from CSF samples of patients with suspected cerebrospinal meningitis in parts of northern Nigeria using metagenomic DNA extracts

Abstract: Background: The most commonly used approaches for detection and characterization of bacterial pathogens of meningitis in developing countries include culture, Gram stain, and latex agglutination. The positivity rate of culture is relatively low due to suboptimal storage and transportation conditions, culture practice, and/or antibiotic treatment administered before specimens are collected. Specimens that yield no growth in culture can still be analyzed using molecular methods, and metagenomic DNA (mDNA) extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…For H. influenzae, Nnadi and colleagues 41 reported H. influenzae type b as the only serotype implicated in their study, while another study 33 reported encountering five serotypes of H. influenzae , including serotypes a ( acsB ), b ( bcsB ) c ( ccsD ), e ( ecsH ), and f ( bexD ).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…For H. influenzae, Nnadi and colleagues 41 reported H. influenzae type b as the only serotype implicated in their study, while another study 33 reported encountering five serotypes of H. influenzae , including serotypes a ( acsB ), b ( bcsB ) c ( ccsD ), e ( ecsH ), and f ( bexD ).…”
Section: Resultsmentioning
confidence: 94%
“… 23 There were 10 articles that fell within this category with prevalence rates ranging from 1.7% to 20.4%. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 Two studies also utilised the molecular approach in the identification of bacterial aetiologies. 25 , 33 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations